Weight of the evidence: independent research projects confirm industry conclusions on the safety of insect-protected maize MON 810. Issue 1 (2nd January 2020) - Petrick, Jay S.; Bell, Erin; Koch, Michael S.
ABSTRACT: The cumulative weight of the evidence demonstrates the safety and equivalence of genetically engineered (GE) crops compared to the conventional varieties from which they have been derived. Confirmatory toxicology and animal nutrition studies have nevertheless become an expected/mandated component of GE crop safety assessments, despite the lack of additional value these studies provide for product safety assessment. Characterization and safety data (e.g. trait protein safety; molecular, compositional, and agronomic/phenotypic assessments), and animal feeding studies form a weight of the evidence supporting the safety of insect-protected maize MON 810. Independent animal testing has recently confirmed the lack of MON 810 toxicity in subchronic and chronic toxicity studies. These results could have been predicted from the available safety data. Animal testing of GE crops should be supported by testable scientific hypotheses and testing should be consistent with ethical obligations to reduce, refine, and replace (3Rs) animal testing when possible.